Adaptive antennas at the mobile and base stations in an OFDM - Kai-Kit Wong (IEEE Transactions on communications)
Several smart antenna systems have been proposed and demonstrated at the base station (BS) of wireless communications systems, and these have shown that significant system performance improvement is possible. We consider the use of adaptive antennas at the BS and mobile stations (MS), operating jointly, in combination with orthogonal frequency-division multiplexing. The advantages of the proposed system includes reductions in average error probability and increases in capacity compared to conventional systems. Multiuser access, in space, time, and through subcarriers, is also possible and expressions for the exact joint optimal antenna weights at the BS and MS under cochannel interference conditions for fading channels are derived. To demonstrate the potential of our proposed system, analytical along with Monte Carlo simulation results are provided